Pengaruh Harga dan Kepercayaan terhadap Loyalitas Pelanggan pada Pembelian Produk di TikTok Shop - Wiwit Fauziah; Wandi Kurniadi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The development of social commerce in Indonesia has driven significant changes in online consumer shopping behavior. Increasingly intense competition among e-commerce platforms requires TikTok Shop to be able to maintain customer loyalty. This study aims to analyze the effect of price and trust on customer loyalty in purchasing products on TikTok Shop. The research employs a quantitative approach using a survey method involving 96 respondents who are active TikTok Shop users. The data analysis technique in this study uses multiple linear regression supported by classical assumption tests. Hypothesis testing is conducted through t-test, F-test, and coefficient of determination analysis. The results show that the price variable has a positive and significant effect on customer loyalty. The trust variable is also found to have a positive and significant effect on customer loyalty. Price and trust simultaneously have a significant influence on customer loyalty with an R² value of 0.523. The findings of this study confirm that an appropriate pricing strategy can increase customer loyalty on TikTok Shop. The enhancement of consumer trust through good service quality also becomes a major factor in maintaining customer loyalty.